1259. Carbapenems Versus Non-carbapenem Beta-Lactams for the Treatment of Ceftriaxone-Susceptible and Piperacillin-Tazobactam-Nonsusceptible Enterobacterales Isolates. (4th December 2021) - Baalbaki, Nadeem; Blum, Sharon; Bosco, Michael; Akerman, Meredith; Zaki, Lana; Johnson, Diane
Abstract: Background: Ceftriaxone-susceptible (CRO-S) and piperacillin-tazobactam-non susceptible (TZP-NS) Enterobacterales isolates have become a frequently isolated phenotype emerging in practice. The genotypic profile is still not clearly elucidated, although prior genotypic sequencing data of these isolates with this phenotypic profile suggests that they are not extended-spectrum beta-lactamase (ESBL) producers. Due to the unfamiliarity with this phenotype and the potential for overuse of broad-spectrum antibiotics, we investigated the clinical outcomes of CRO-S/TZP-NS isolates with carbapenem versus non-carbapenem beta-lactam (NCBL) therapy. Methods: This was a retrospective chart review of patients with a diagnosed infection caused by a CRO-S/TZP-NS Enterobacterales isolate admitted to any of the three NYU hospitals: Long Island, Tisch, or Brooklyn campuses, treated with a beta-lactam (BL) antibiotic from October 2015 to October 2020. The primary outcome was treatment failure defined as an escalation of antibiotics due to clinical worsening, 30-day all-cause mortality, or relapse of infection with the same genus and species. Patients who received ≥ 72 consecutive hours of BL antibiotics were considered to be on definitive therapy. Results: A total of 111 patients were included in this study, 9 in the carbapenem group and 102 in the NCBL group. There was no statistically significant difference in the clinical failure rate between the two groups (0% vs 10.8% respectively, P=0.56). A univariate analysis assessed the association of clinical failure with TZP, CRO, cefpodoxime, cefepime, and 1 st -3 rd generation cephalosporins grouped. There were no statistically significant increases in 30-day treatment failure in any of the individual categories. Conclusion: There were no statistically significant differences in 30-day failure with the use of carbapenem vs NCBL antibiotics. No individual BLs or classes were associated with an increased risk of clinical failure. This study suggests that there is a role for NCBL antibiotics for Enterobacterales isolates with this phenotypic presentation and supports prior data that they are less likely to be ESBL producers. Prospective studies are warranted to confirm these findings. Disclosures: All Authors : No reported disclosures